A Simple and Effective GPS Receiver Autonomous Integrity Monitoring and Fault Isolation Approach - Ershen Wang; Ming Cai; Tao Pang (2012 International Conference on Control Engineering and Communication Technology, 2012)
Receiver Autonomous Integrity Monitoring (RAIM) for Global Positioning System (GPS) is required for safety and liability critical applications such as aircraft no precision approach, river and harbour navigation real-time or kinematic surveying, etc. A simple and effective approach for RAIM is given for fault detect and isolation on GPS receiver. The method is based on the pseudorange residual data of GPS receiver. The pseudorange residual data for each satellite in the navigation solution is used to compute the sum of squares residuals as decision variables. In order to decide whether or not the corresponding navigation measurement will exist fault, the value is compared to the thresholds that have been set to satisfy the integrity requirements. If any time five measurements are available, a fault can be detected quickly by testing to see if it exceeds the thresholds. When six or more satellites are available, a single measurement fault can be isolated. The validation and analysis based on the real GPS data show that the method is feasible and practical. And it is convenient to be embedded in the GPS receiver for fault detect and isolation.